2020
DOI: 10.1111/jnu.12595
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Reporting in Nursing Research: Addressing a Common Error in Reporting of p Values (p = .000)

Abstract: Statistical science is paramount in scientific research that could be utilized at any stage of a scientific study (Gunel Karadeniz et al., 2019). The correct use of statistics has long been highlighted by journals, editorials, and researchers because the misuse and misinterpretation of statistics may cause research to lose its importance (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…However, the redundant expression may mislead readers. In a study that examined 30 main nursing journals 8) , it was found that "p = 0.000," which is an error, was documented in 93.3% of the journals. Documenting p = 0.000 was likely due to the author wanting to strongly emphasize that the results obtained were significant.…”
Section: Notation Of P-valuesmentioning
confidence: 99%
“…However, the redundant expression may mislead readers. In a study that examined 30 main nursing journals 8) , it was found that "p = 0.000," which is an error, was documented in 93.3% of the journals. Documenting p = 0.000 was likely due to the author wanting to strongly emphasize that the results obtained were significant.…”
Section: Notation Of P-valuesmentioning
confidence: 99%